1988
DOI: 10.1099/00221287-134-2-473
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Reaction of Guinea-pigs Following Intranasal Mycoplasma pneumoniae Infection and Immunization with the 168 kDa Adherence Protein

Abstract: Humoral responses to Mycoplasma pneumoniae proteins, especially the 168 kDa protein, were demonstrated by Western blotting in sera and bronchial washings of all groups of infected or immunized guinea-pigs. However, infection was not prevented by these local and systemic antibodies. Hilar lymphocytes of infected and immunized guinea-pigs were stimulated in vitro by sonicated M. pneumoniae antigen and by the 168 kDa protein. Stimulation was significantly lower in animals which had been infected twice or had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Similar problems were encountered with temperature-sensitive mutant vaccines (51,172,388,389). Other vaccine candidates have included acellular protein and polysaccharide components and recombinant DNA (50,52,123,204,206). While the importance of the P1 adhesin in mediating M. pneumoniae cytadherence and initiation of disease cannot be denied, animal studies using P1 as a vaccine antigen have not demonstrated protective efficacy (76,(204)(205)(206).…”
Section: Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar problems were encountered with temperature-sensitive mutant vaccines (51,172,388,389). Other vaccine candidates have included acellular protein and polysaccharide components and recombinant DNA (50,52,123,204,206). While the importance of the P1 adhesin in mediating M. pneumoniae cytadherence and initiation of disease cannot be denied, animal studies using P1 as a vaccine antigen have not demonstrated protective efficacy (76,(204)(205)(206).…”
Section: Vaccinesmentioning
confidence: 99%
“…Other vaccine candidates have included acellular protein and polysaccharide components and recombinant DNA (50,52,123,204,206). While the importance of the P1 adhesin in mediating M. pneumoniae cytadherence and initiation of disease cannot be denied, animal studies using P1 as a vaccine antigen have not demonstrated protective efficacy (76,(204)(205)(206). Experimental animal studies involving mice (449,450) hamsters (18,(75)(76)(77), guinea pigs (206), and chimpanzees (21,153) have continued through the 1980s and 1990s, but to our knowledge there have been no recent clinical trials in humans with any newer versions of M. pneumoniae vaccines, and there is no indication that any type of vaccine will be approved for use against M. pneumoniae any time soon.…”
Section: Vaccinesmentioning
confidence: 99%
“…The spectrum of vaccines examined includes killed whole-cell vaccines (formalin), live temperaturesensitive mutants, polysaccharide extracts, protein extracts, and single component vaccines e.g. P1 vaccine (2,18). A large number of studies in both animal models and humans led to the recognition of several important findings.…”
Section: Discussionmentioning
confidence: 99%
“…Among their investigations, experimental animal infections were successful and these findings were integral to the development of better-defined animal models when the etiological agent could be artificially cultivated (9,11). Recent studies have favored the golden Syrian hamster or the guinea pig as hosts in the model systems (3,18), and a spectrum of histopathological scoring schemata has been employed to describe the pulmonary pathology (3,14,15,18,26). Despite the apparent fact that M. pneumoniae is not a natural pathogen in the aforementioned animals, the nature of the histopathology after experimental infection is analogous to that recorded for human pulmonary infection (24).…”
mentioning
confidence: 99%
“…Live vaccines composed of M. pneumoniae strains attenuated by continuous passages in vitro or temperature-sensitive mutants protected hamsters, but are unsuitable for human use because they retained partial virulence or decreased immunogenicity (4, 12). A current approach to vaccine development is based on producing cell extract vaccines made of defined cell components of the pathogen (5-7), especially the disease-related and virulence-related antigenic components, such as the attachment protein P1 (17,18). It is not clear whether a vaccine made entirely of the P1 protein would be effective in protection against M. pneumoniae disease.…”
mentioning
confidence: 99%